Human cellular restriction factors that target SARS-CoV-2 replication - Marivate, Amukelani; Bekker, Shani; Fish, Muhammad Qasim; Mosebi, Salerwe (Frontiers in Virology, 2024)
Millions of people have died and a worldwide economic catastrophe has been brought on by the coronavirus disease 2019 (COVID-19) pandemic. Infections caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may presently be treated with less than 10 antiviral drugs such as Remdesivir. The need for medical intervention due to sickness has led to unprecedented research efforts to study the biology of coronaviruses. Additionally, there is a strong likelihood that coronaviruses will cause pandemics in the future. All viruses cannot replicate optimally due to host restriction factors. Given that they are genetically more stable than viral targets and may be shared by similar viruses, these antiviral host factors provide appealing targets for antiviral treatment. The identification of antiviral host factors that are a component of human innate immunity and that prevent the completion of the SARS-CoV-2 life cycle has been made possible by the deployment of several “omics” technologies. In this review, we provide an overview of the antiviral host factors that limit the replication of SARS-CoV-2 in this, which were mostly discovered using functional genetic and interactome screening. Important cellular mechanisms for the SARS-CoV-2 life cycle are covered. Finally, we highlight host restriction factors that could be targeted by clinically approved molecules and the induction of these factors as potential antiviral therapies for COVID-19.